Use of vibration measurements to determine the most suitable locations to improve sound insulation in buildings - Rosão, Vitor (2014)
In the present work in situ sound insulation measurements were performed, according to the applicable standards of ISO 140 series, and vibration measurements of the separator elements in question (floor, ceiling, side walls). We intend to compare the results of direct measure-ments of sound insulation with the results of the predictions of sound insulation, based on the vibration measurements, to verify the feasibility of using vibration measurements to determine the most suitable locations of sound propagation (floor, ceiling, side walls) to act in order to improve, where it is needed, sound insulation in buildings. The principles of sound propaga-tion considered in EN 12354 series standards are used, e.g., 5 major structural paths, depend-ing on the sound radiating element in the receiver compartment [1) partition wall, 2) ceiling, 3) floor, 4) wall left side, 5) wall right side] and 2 major airborne path [1) openings in the par-tition element, 2) openings in other elements]. Different Radiation Factors, to convert vibra-tion of elements in sound are also considered, depending on the radiation element type and on the frequency in question.